Characterization of Cochlear, Vestibular and Cochlear-Vestibular Electrically Evoked Compound Action Potentials in Patients with a Vestibulo-Cochlear Implant - Nguyen, T. A. K.; Cavuscens, Samuel; Ranieri, Maurizio; Schwarz, Konrad; Guinand, Nils; van de Berg, Raymond; van den Boogert, Thomas; Lucieer, Floor; van Hoof, Marc; Guyot, Jean-Philippe; Kingma, Herman; Micera, Silvestro; et al. (Frontiers in Neuroscience, 2017)
The peripheral vestibular system is critical for the execution of activities of daily life as it provides movement and orientation information to motor and sensory systems. Patients with bilateral vestibular hypofunction experience a significant decrease in quality of life and have currently no viable treatment option. Vestibular implants could eventually restore vestibular function. Most vestibular implant prototypes to date are modified cochlear implants to fast-track development. These use various objective measurements, such as the electrically evoked compound action potential (eCAP), to supplement behavioral information. We investigated whether eCAPs could be recorded in patients with a vestibulo-cochlear implant. Specifically, eCAPs were successfully recorded for cochlear and vestibular setups, as well as for mixed cochlear-vestibular setups. Similarities and slight differences were found for the recordings of the three setups. These findings demonstrated the feasibility of eCAP recording with a vestibulo-cochlear implant. They could be used in the short term to reduce current spread and avoid activation of non-targeted neurons. More research is warranted to better understand the neural origin of vestibular eCAPs and to utilize them for clinical applications.